2012
DOI: 10.1097/01.sa.0000415036.42096.45
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Guidewire-Assisted Nasogastric Tube Insertion in Anesthetized and Intubated Patients

Abstract: D ifficult and failed tracheal intubations are one of the principal causes of anesthetic-related mortality and morbidity. Difficult intubations are common in obese patients because the limited oropharyngeal space may impede adequate visualization. With the increase in numbers of obese and morbidly obese patients, the incidence of difficult intubations is also likely to rise. The Pentax AWS (Ambu A/S, Ballerup, Denmark) is a video laryngoscope designed to facilitate intubation by providing a video image of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…Kirtania et al observed higher rate of successful NGT insertion in esophageal guide wire-assisted Technique compare to conventional technique (99.2% vs 56.7%). 11 The success rates of NGT insertion in the first attempt in our study was 98%. This difference may be due to sample of patients in Kirtania study which was much larger than ours.…”
Section: Years) Demographic Variables Of Patients Was Demonasteratedsupporting
confidence: 46%
“…Kirtania et al observed higher rate of successful NGT insertion in esophageal guide wire-assisted Technique compare to conventional technique (99.2% vs 56.7%). 11 The success rates of NGT insertion in the first attempt in our study was 98%. This difference may be due to sample of patients in Kirtania study which was much larger than ours.…”
Section: Years) Demographic Variables Of Patients Was Demonasteratedsupporting
confidence: 46%
“…Appukutty et al [ 17 ] compared a slit endotracheal tube and guidewire with the conventional method and showed similar success rates. Kirtania et al [ 23 ] showed that the esophageal guidewire-guided technique with a manual shift of the larynx resulted in correct NGT placement in anesthetized patients and had a low incidence of complications and comparatively shorter insertion times.…”
Section: Resultsmentioning
confidence: 99%
“…These attempts include the use of slit endotracheal tubes, forward displacement of the larynx, use of various forceps, use of a ureteral guidewire as a stylet, head flexion, and lateral neck pressure. [2][3][4][5] Visualization-aided modalities were recently developed to facilitate NGT insertion, 1,6 and studies have been performed to examine the role of modified Magill forceps, which have angles similar to those of the GlideScope blade (Verathon, Bothell, WA, USA) (Figure 1). 7 The purpose of this study was to investigate whether the GlideScope and modified Magill forceps facilitate NGT insertion in patients under general anesthesia who have undergone endotracheal tube insertion.…”
Section: Introductionmentioning
confidence: 99%